Examining the Role of Islamic Communication Ethics, Digital Literacy, and Cross-Cultural Communication Competence in Shaping Global Talent Development in the Digital Era - NASIDI, QARIBU YAHAYA; Abubakar, Ahmed; Alhassan, Musa; Hassan, Isyaku (Journal of Contemporary Issues in Media & Communication (JCIMC), 2025)
This study examines the role of Islamic Communication Ethics, Digital Literacy, and Cross-Cultural Communication Competence in shaping Global Talent Development in the digital era, focusing on Nigeria and Malaysia. A quantitative research design was employed, and data were collected from 500 respondents using a structured questionnaire. SmartPLS was used for data analysis. The results demonstrated that Cross-Cultural Communication Competence had a strong and significant positive effect on Global Talent Development (? = 0.849, p < 0.001), highlighting the importance of cultural adaptability in preparing individuals for success in a globalised workforce. Digital Literacy showed a significant but negative relationship (? = -0.099, p = 0.009), suggesting that technical skills alone may not translate directly into talent growth unless integrated with soft skills and cultural awareness. Islamic Communication Ethics had a positive but statistically insignificant effect (? = 0.082, p = 0.106), indicating that its influence may be more indirect or context-dependent. These findings underscore the need for an integrated approach to talent development that combines cultural competence, digital literacy, and ethical Communication. For Nigeria and Malaysia, universities, organisations, and policymakers should focus on cross-cultural training, ethics-based professional development, and aligning digital skills with global workplace requirements. By adopting such a holistic strategy, both nations can better prepare their workforce to thrive in the competitive, interconnected, and ethically complex global economy.